Cyclooxygenase-2 (COX-2) as a Target of Anticancer Agents: A Review of Novel Synthesized Scaffolds Having Anticancer and COX-2 Inhibitory Potentialities - Noor ul Amin Mohsin; Sana Aslam; Matloob Ahmad; Muhammad Irfan; Sami A. Al-Hussain; Magdi E. A. Zaki (MDPI AG, 2022)
Cancer is a serious threat to human beings and is the second-largest cause of death all over the globe. Chemotherapy is one of the most common treatments for cancer; however, drug resistance and severe adverse effects are major problems associated with anticancer therapy. New compounds with multi-target inhibitory properties are targeted to surmount these challenges. Cyclooxygenase-2 (COX-2) is overexpressed in cancers of the pancreas, breast, colorectal, stomach, and lung carcinoma. Therefore, COX-2 is considered a significant target for the synthesis of new anticancer agents. This review discusses the biological activity of recently prepared dual anticancer and COX-2 inhibitory agents. The most important intermolecular interactions with the COX-2 enzyme have also been presented. Analysis of these agents in the active area of the COX-2 enzyme could guide the introduction of new lead compounds with extreme selectivity and minor side effects.